Cost Efficiency Analysis in French Banking Sector - ZHANG, SHIJIE (2016)
By using the stochastic frontier approach, this study evaluates the cost efficiency of 122 French commercial banks over the period 2005 to 2014. The main objective is not only to inherit previous studies on efficiency analysis of French banks, but also extend to measure the cost efficiency level of French banking sector after experiencing a series of financial events (2005-2014). On average, the cost efficiency score ranges from 76.55% to 67.88%, showing a decreasing tendency over time. Meanwhile, this paper also investigates the determinants of cost efficiency level by using Tobit regression model. The findings suggest that the GDP growth can improve bank cost efficiency while inflation rate has negative impact on cost efficiency of French banks. For international factors, bank size, asset quality, credit risk and profitability significantly influence the cost efficiency level of banks in France.